EFEKTIVITAS PELAYANAN RUMAH SINGGAH PEDULI CABANG BANDUNG - Andhika Ligar Hardika; Radhi Abdul Halim Rachmat; Daniel Nababan; Hafied Noor Bagja; Rudy Lizwaril (LPPM Universitas Bina Bangsa, 2024)
Rumah Singgah Peduli is a house of social activities which operates in the humanitarian sector to facilitate health facilities. This activity provides facility services for patients from outside Bandung and throughout Indonesia who need temporary accommodation for examinations, operations and health services. Community service uses qualitative methods with a descriptive approach. Based on the results that have been obtained, it shows that the effectiveness of the program implemented by Rumah Singgap Peduli, especially in the health sector, has run well and is on target. Community satisfaction (patients and companions) with the services provided shows that the program is very helpful and needed for those who are among the poor